Implementasi Data Mining Untuk Pengaturan Layout Swalayan Delimas Lestari Kencana Dengan Menggunakan Dengan Menggunakan Algoritma K-Means Clustering - Dwi Retno Lestari (JURIKOM (Jurnal Riset Komputer), 2019)
Supermarkets are one of the shopping places that can provide comfort, cleanliness, speed and neatness of products for consumers. Many consumers prefer shopping at supermarkets than in traditional markets because supermarkets can provide comfort and neatness of their products, but not a few of consumers complain about product layout in supermarkets. Determination of product layout (layout) at supermarkets is an important thing that must be considered by the supermarket management. In this thesis, we will explain how the implementation of the k-means clustering algorithm is based on consumer shopping habits to produce a product brand layout based on the type of product. This study uses data obtained from shopping receipts at the Delimas Lestari Kencana Lubuk Pakam supermarket. K-means clustering algorithm is used to partition data into clusters so that data that has the same characteristics is grouped into one and the same cluster of data that has different characteristics grouped into other groups. The results of this study produce a product brand layout (layout) based on the type of product that can facilitate consumers in getting the needed items.